Sanctions as a Socio-Political Factor of International Cooperation (on the Example of the Influence of Modern Russian-German Relations on the International System) - A. P. Nagdaseva (Дискурс)
Introduction. The research work defines the current significance of international sanctions, examines the types of sanctions, the goals of their imposition and the consequences for the international system. As an example, anti-Russian sanctions and retaliatory measures are being analyzed, as well as their influence on relations between the states. In the study an assessment of the development of Russian-German cooperation in various fields before and after the imposition of sanctions is given.Methodology and sources. Such research methods as analysis, synthesis, comparison, statistical methods are used in the research work. Import-export relations between Russia and Germany are analyzed in the paper.Results and discussion. Russia incurs heavy losses from sanctions compared to the European Union. Anti-Russian sanctions do not contribute to the development of free international trade. The European Union is having difficulty maintaining transatlantic economic relations. The imposition of US extraterritorial sanctions is detrimental to German and other European companies. Both European countries and Russia have internal problems, which are aggravated by the sanctions confrontation.Conclusion. Despite all the existing problems and obstacles that stand in the way of bilateral relations, there are positive trends in them. Russia and Germany, in general, have adapted to the sanctions regime. Anti-Russian sanctions will probably not be lifted in the short term.